Generative literature analysis on the rise of prosumers and their influence on the sustainable energy transition - Oprea, Simona-Vasilica; Bâra, Adela (Utilities policy, 2024)
This study delves into the scholarly discourse surrounding prosumers, aiming to chart their historical progression and explore the primary topics that have garnered attention in scientific research. While the concept first appeared in academic literature in 1986, a significant surge in interest was observed starting in 2010, with momentum steadily increasing to the present day. Utilizing the Latent Dirichlet Allocation (LDA) method to examine the abstracts of nearly 1400 publications indexed in the Web of Science, this research uncovers three principal subjects that dominate academic inquiry related to prosumers: grid connection and system integration, market and technologies. •Prosumers – the unit of energy communities – insights over the last decades.•Top 5 keywords: prosumer, smart grid, demand response, optimization and blockchain.•Generative models: Latent Dirichlet Allocation to examine text and extract topics.•3 topics: technical & operational aspects, market dynamics and exploration of new technologies.